A multi-case study of accelerated trajectories of science talent development: Matthew effects re-examined. (May 2023) - Dai, David Yun; Li, Xian
Matthew effect ("the rich get richer") has been a research topic for decades. It refers to a cumulative advantage, social or individual, in talent development as well as performance or productivity, typically unfolding longitudinally. The present study builds on a previous qualitative study as an attempt to fully understand developmental underpinnings of an accelerated science career, with a focus on developmental changes as potential explanations for the observed Matthew effects. In contrast to traditional theoretical explanations that resort to either social or individual advantages, the present study, in light of Evolving Complexity Theory (ECT), uncovered developmental changes as potentially responsible for a distinct accelerated career trajectory and the apparently unfolding Matthew effects. Implications of the findings in terms of understanding the role of evolving individuality for talent development are discussed.